Population regulation of African buffalo in the Mara–Serengeti ecosystem - Dublin, H.T.; Ogutu, Joseph O. (Commonwealth Scientific and Industrial Research Organisation, 2015)
Context: The processes regulating ungulate populations have been the focus of numerous studies. For the African buffalo (Syncerus caffer Sparrman) population inhabiting the Mara–Serengeti ecosystem, rinderpest was the primary regulatory factor up to the mid-1960s. Following reduction of rinderpest and buffalo population increase, interspecific competition for food, notably with cattle and wildebeest (Connochaetes taurinus Burchell), was thought to be the primary regulatory factor in the ecosystem. Aims: We analysed buffalo population trends and the relationship between buffalo population growth and rainfall and density dependence in the Mara–Serengeti ecosystem and discuss the findings in the context of the key ecosystem processes governing buffalo population dynamics in African savannas, namely, food limitation, competition, predation, disease and land use changes. Methods: We analysed buffalo population dynamics in the Mara–Serengeti ecosystem in relation to rainfall and density dependence feedback between 1984 and 2010. Key results: Buffalo population growth was both significantly density-dependent and positively correlated with the dry season rainfall after, but not before, a severe drought in 1993. Buffalo numbers crashed by 48.6% in 1984–85 and by 76.1% in 1993–94 during severe droughts when food availability was lowest and competition with the more numerous cattle and wildebeest was highest. Conclusions: Recovery of buffalo numbers to pre-drought levels took 8–9 years after the 1984–85 drought but was much slower, with buffaloes numbering merely 36% of their 1993 population (12 895 animals) 18 years after the 1993–94 drought despite intermittent periods of high rainfall, probably due to demographic and/or reproductive factors, heightened competition with livestock, land use changes in the adjoining pastoral ranches, lion predation and recurrent severe droughts. Implications: Our findings demonstrate how food limitation caused by droughts associated with the hemispheric El Niño–Southern Oscillation can cause severe declines in and threaten the persistence of large ungulate populations. The findings also portray how density-dependent food limitation, competition, predation, land use changes and other factors can accentuate the effect of droughts and greatly prolong population recovery.